30 Elite irrigated lowland breeding lines which out-yielded ISRIZ-07 and Sahel 108 by up to 47% identified in Senegal - CGIAR Research Program on Rice (2020)
In a Preliminary Yield Trial (PYT) conducted with 75 entries, 21 lines with yield advantages of 5.38 - 15.38% compared to check variety Sahel 108 (8.8 t/ha) were identified at Ndiaye, Senegal.